ENDOPARASITES AS ENVIRONMENTAL QUALITY INDICATORS IN WILD BIRDS IN TINGUÁ BIOLOGICAL RESERVE, RIO DE JANEIRO, BRAZIL - Ribeiro Luz, Hermes (2014)
Wild birds are hosts of a variety of parasites. Their migratory behavior increases the dispersion of parasites and consequently the occurrence of diseases in various locations around the world. To identify the parasitological fauna of wild birds in the Tinguá Biological Reserve in Rio de Janeiro state-Brazil, 43 birds belonging to the orders Passeriformes and Columbiformes were captured and stool samples collected. Four birds (9.3%) were positive for parasites. In the fecal samples, trematode eggs of the Tanaisia sp and oocysts of coccidia as Isospora sp were found. The low parasite prevalence in wild birds found in this study may be an environmental quality indicator,because the reserve is a preserved area that has little human interference. We emphasize also thatthe use of the technique of collecting stool samples with anal swabs was successful for diagnostic purposes.